PISA-LIKE PROBLEMS USING THE CONTEXT OF SWIMMING SPORTS IN ASIAN GAMES - Putra, Eko Septiansyah; Putri, Ratu Ilma Indra; Susanti, Ely (Journal on Mathematics Education)
This study aimed to produce items of PISA mathematics using the context of swimming sports that was valid, practical and had potential effects of the problem on students mathematical literacy ability. The method used was designed research type development study. This method consisted of two stages, preliminary and formative evaluation. The data collection techniques used walkthrough interviews, documentation, and tests. The items were validated by four experts for the expert review and three students on one-to-one. The validity of this developed problem was seen from its compatibility with the PISA framework. Practicality seen from small group test results involved six students. The developed items were practical because they were easily understood and used by the students. The potential effects were identified based on the analysis of students answers on the field test stage. The field test was conducted in SMA Negeri 1 Palembang for 31 students. The results of this study generated PISA-like problems using the context of swimming sports that were valid, practical and had potential effects on students mathematical literacy skills. In this study, the students mathematical literacy skills arose to include mathematical ability, reasoning and argumentation ability, and ability to choose strategies to solve problems